Epistemology as a Scientific Methodology Foundation for the Development of New Theories in the Field of Islamic Education Management - Iwan Setiawan; Anis Fauzi; Moh Suhri Rohmansyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the process of observing to satisfy human curiosity, it is carried out in certain ways, certain methods, by the process of scientific activities, especially in Islamic education management. Method as a way to observe a process of scientific activity. The method as a way to observe something, the process of scientific activity, must also be in certain ways, which can be justified as a scientific activity. The scientific method is a procedure in obtaining knowledge which is called science. scientific knowledge born of the scientific method in order to become scientific truth. Scientific truth is a clear and definite knowledge of the truth according to scientific norms. Epistemology is a philosophy of science that is reasoning or thought, the scientific method and scientific truth are part of the scope of the philosophy of science in the new theory of Islamic education management